Direct access to N-alkylated amines and imines via acceptorless dehydrogenative coupling catalyzed by a cobalt(ii)-NNN pincer complex - Midya, Siba P.; Pitchaimani, Jayaraman; Landge, Vinod G.; Madhu, Vedichi; Balaraman, Ekambaram (Catalysis Science & Technology, 2018)
A simple, phosphine-free Co(ii)-NNN pincer complex catalyzed direct N-alkylation of anilines with alcohols via hydrogen auto-transfer (HA) and selective acceptorless dehydrogenative coupling (ADC) of benzylamines with alcohols affording imines with the liberation of molecular hydrogen and water is reported.

Ni-catalyzed alpha-alkylation of unactivated amides and esters with alcohols by hydrogen auto-transfer strategy - Midya, Siba P.; Rana, Jagannath; Pitchaimani, Jayaraman; Nandakumar, Avanashiappan; Madhu, Vedichi; Balaraman, Ekambaram (CHEMSUSCHEM, 2018)
A transition-metal-catalyzed borrowing hydrogen/hydrogen auto-transfer strategy allows the utilization of feedstock alcohols as an alkylating partner, which avoids the formation of stoichiometric salt waste and enables a direct and benign approach for the construction of C-N and C-C bonds. In this study, a nickel-catalyzed alpha-alkylation of unactivated amides and ester (tert-butyl acetate) is carried out by using primary alcohols under mild conditions. This C-C bond-forming reaction is catalyzed by a new, molecularly defined nickel(II) NNN-pincer complex (0.1-1 mol %) and proceeds through hydrogen auto-transfer, thereby releasing water as the sole byproduct. In addition, N-alkylation of cyclic amides under Ni-catalytic conditions is demonstrated.

Phosphine-free cobalt pincer complex catalyzed Z-selective semi-hydrogenation of unbiased alkynes - Landge, Vinod G.; Pitchaimani, Jayaraman; Midya, Siba P.; Subaramanian, Murugan; Madhu, Vedichi; Balaraman, Ekambaram (Catalysis Science & Technology, 2018)
Herein, we report a novel, molecularly defined NNN-type cobalt pincer complex catalyzed transfer semi-hydrogenation of unbiased alkynes to Z-selective alkenes. This unified process is highly stereo-and chemo-selective and exhibits a broad scope as well as wide functional group tolerance. Ammonia-borane (AB), a bench-stable substrate with high gravimetric hydrogen capacity, was used as a safe and practical transfer hydrogenating source.